ACE inhibitors unmask incoordinate diastolic wall motion in restrictive left ventricular disease. Issue 4 (October 1996) - Henein, M. Y.; Amadi, A.; O'Sullivan, C.; Coats, A.; Gibson, D. G.
Abstract : OBJECTIVE: To assess the effect of ACE-inhibition on left ventricular filling and wall motion in patients with a clinical diagnosis of heart failure. DESIGN: Prospective examination of left ventricular systolic and diastolic function using M mode echocardiography and pulsed and continuous wave Doppler before and three weeks after starting an ACE inhibitor. SETTING: A tertiary referral centre for cardiac disease equipped with non-invasive facilities. SUBJECTS: 30 outpatients with a clinical diagnosis of heart failure in whom treatment with an ACE inhibitor was started; age 61 (SD 11) years; 27 male; 3 female; 21 healthy controls of similar age. RESULTS: Left ventricular cavity was dilated both at end systole and end diastole, and fractional shortening reduced. Although mean isovolumetric relaxation time (IVRT) and transmitral E (early) to A (late) filling velocity (E/A) ratio were not different from normal, a value of 1.0 on the normal frequency plot of the E/A ratio divided the patients bimodally into two groups: 20 patients (group A) with E/A ratio > 1.0 and 10 patients (group B) < 1.0. In group A patients, IVRT was short as was transmitral E wave deceleration time compared to normal (P < 0.001), fulfilling the criteria of restrictive left ventricular physiology. Left ventricular wall motion during IVRT was coordinate and left ventricular end diastolic pressure was raised on the apex-cardiogram (P < 0.001). In group B, E wave deceleration time was longer, relaxation incoordinate, and apexcardiogram normal. With an ACE inhibitor: in group A, left ventricular dimensions fell at end diastole (P < 0.05) and end systole (P < 0.01) but fractional shortening did not change; long axis total excursion (P < 0.01) and peak rate of shortening (P < 0.05) both increased; IVRT increased (P < 0.001) with the appearance of markedly incoordinate wall motion, minor axis lengthening, and long axis shortening (P < 0.001 for both); A wave amplitude also consistently increased (P < 0.001); finally, transmitral E wave velocity fell and A wave velocity increased. ACE inhibition did not alter any of the left ventricular minor and long axis or transmitral Doppler variables in patients in group B. CONCLUSIONS: Patients with a clinical diagnosis of heart failure differ in their presentation and response to ACE inhibition according to baseline haemodynamics. In restrictive left ventricular physiology, ACE inhibition reduces cavity size and prolongs IVRT, compatible with a fall in left atrial pressure. At the same time, ventricular relaxation becomes very delayed and incoordinate, greatly reducing early diastolic left ventricular filling velocity. Thus ACE inhibition unmasks major diastolic abnormalities in patients with restrictive left ventricular disease.